High precision studies of the electronic properties in high-Tc La2-xBaxCuO4 and skutterudite LaOs4Sb12 superconductors - Tee, Xian Yang (2015)
High temperature superconductors (HTS) are not well understood despite intensive research over the past three decades. Recently, the stripe phase which is a form of charge and spin density modulation has received more attention due to its prevalence in these systems. However, the effects of stripes on the electronic properties of HTS have remained elusive, and new experimental results are needed to shed light on this pressing matter. In this Thesis, we develop several experimental setups and data analysis methods to perform high-precision magneto-transport experiments including electrical resistivity, thermopower, Nernst effect, and other specially designed measurements for temperatures down to 5 K and magnetic fields up to 16 T. These methods enabled us to perform systematic investigations on La2-xBaxCuO4 where stripe correlations are known to be the strongest among HTS families. Our experimental results demonstrate that in this high-Tc family, the surface and the bulk of the same sample exhibit two distinct and tunable superconducting transition temperatures, with the value at the surface significantly enhanced – up to 64% relative to the bulk of the sample for the materials we studied. Notably, the occurrence of this novel effect coincides with that of the stripe order, suggesting a possible link between the two. The effects of stripes on superconducting fluctuations and quasiparticle transport are further investigated with Nernst effect measurements. Several unusual features are observed which are discussed in the context of superconducting stripes with preferred spatial arrangements. The latter part of this Thesis focuses on developing a tunnel-diode-oscillator setup for the measurement of magnetic penetration depth on unconventional superconductors. This technique can be optimized for a part-per-billion precision level which makes it very useful in addressing several fundamental problems such as the determination of pairing symmetry. In particular, its compatibility with dilution refrigerator makes it a valuable probe for low-Tc materials such as heavy-fermion systems. During the construction of the setup, we analyzed earlier penetration depth data of skutterudite superconductor LaOs4Sb12 in order to obtain guidance on the physics and parameters required for the abovementioned apparatus. Our results indicate multiband s-wave superconductivity in this compound. The finding is further discussed in reference to the unconventional pairing symmetry observed in the closely related material PrOs4Sb12.